Hepatitis B e Antigen Seroconversion Is Related with the Function of Dendritic Cells in Chronic Hepatitis B Virus Infection - Chunjing Lin; Hai Zou; Shumin Wang (Gastroenterology Research and Practice)
Aim. To investigate the relationship between hepatitis B e antigen seroconversion and the function of dendritic cells (DC) in patients with hepatitis B virus. Methods. The peripheral blood mononuclear cells (PBMC) from 21 chronic HBV patients in immune tolerance state, 23 patients in inactive HBsAg carrier state, and 10 healthy HBV-naive blood donors were incubated and induced into DC in presence of granulocyte-macrophage colony stimulating factor (GM-CSF) and interleukin-4 (IL-4), respectively. The expressions of surface markers on DC were detected by flow cytometry, and the stimulatory capacity of DC in allogenic mixed leukocyte reaction (MLR) was tested by CCK-8, and the level of cytokines released by DC was analyzed by enzyme-linked immunosorbent assay (ELISA). Results. DC from patients in immune tolerance showed a remarkably lower surface expression of CD80, CD86, and HLA-DR and exhibited an impaired stimulatory capacity in MLR and reduced secretion of IL-12, as compared to the patients in inactive HBsAg carrier state. There was no significant difference between the indicators from the patients in inactive HBsAg carrier state and healthy subjects. There was a significant difference of HBV DNA level between immune tolerance and inactive HBsAg carrier group (P<0.01) and a negative correlation between HBV DNA level and the expressions of dendritic cells in both groups, respectively (P=0.01). Conclusion. DC from patients in inactive HBsAg carrier state shows stronger function in comparison with patients in immune tolerance, the expressions of dendritic cells correlate with HBV DNA level, and the function stage of DC may play an important role in HBeAg seroconversion.